Pemetaan Dan Perancangan Jaringan Komputer Di Gedung Rektorat Baru Di Iain (Institut Agama Islam Negri) Surakarta - Hariyudo, Reza Rizqi Firdaus; , Fatah Yasin Al Irsyadi, S.T., M.T (2017)
Computer network design is an important instrument of ucational institution, including IAIN Surakarta. In order to maximize the human resource's work, the IAIN Surakarta applied the computer network system which is compulsory in order to manage the administration and teaching-learning process. The effort demands to the better network system that manages the sharing information between employees in IAIN Surakarta. The study used a simulation and plementation method. The data was collected from literature review, observation and interview. The computer network design that has been applied in the Rectory Building of IAIN Surakarta will be presented in Cisco Packet Tracer. The result of the research is the network design that is used in rectory building of IAIN Surakarta. The network design is able to support the staffs and lecturers in IAIN Surakarta. The design has been done with minimum utilities, so that will be easier to develop better service in the network.